Changing Borders, Rethinking Sovereignty: Towards a Right to Migrate - Casas-Cortes, Maribel (2015)
The intervention of European Union border authorities in countries of Africa, Asia and Eastern Europe has shown how the European state “border” has been displaced from its national moorings and externalized across the territories of neighboring states. Our research examines the outsourcing of the southern European Union border, focusing on the case of Spain and its relationship with Morocco and countries of Western Africa. In this paper we describe the development and implementation of this strategy of migration management, signaling implications of border externalization from the point of geopolitics and legality, including a suggestive call to reclaim the legal tradition of the Right to Migrate. A intervenção das autoridades fronteiriças da União Europeia em países da África, da Ásia e do Leste Europeu tem mostrado como a “fronteira” do estado Europeu tem sedescoladode suas delimitações nacionais e seexteriorizadoaos territórios dos estados vizinhos.Nossa pesquisa examina a terceirização da fronteira sul da União Europeia, com enfoque no caso da Espanha e de seu relacionamento com o Marrocos e os países do oeste africano. Neste trabalho, descrevemos o desenvolvimento e a implementação dessa estratégia de gerenciamento da migração, sinalizando as implicações da exteriorização de fronteira do ponto de visto geopolítico e jurídico, incluindo uma recomendação dese recuperar a tradição legal do Direito de Migrar.